2020
DOI: 10.5502/ijw.v10i4.935
|View full text |Cite
|
Sign up to set email alerts
|

Winter is coming: Wintertime mindset and wellbeing in Norway

Abstract: Previous research of the effect of winter on wellbeing has yielded contradictory findings. While there is evidence that the lack of sunlight in wintertime can lead to seasonal depression and negative emotions, many individuals are able to thrive during the winter. What might determine whether the darkness of winter leads to poor psychological outcomes? To investigate whether or not mindset contributes to wintertime wellbeing, we assessed wintertime mindset via a Wintertime Mindset Scale measuring attitudes tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Harmatz et al ( 2000 ) found depression, hostility, anger and irritability are highest in winter and lowest in summer with females having stronger seasonal variation in wellbeing than males. Some link seasonal variance on wellbeing, to variance in daylight hours and weather conditions, although wellbeing responses to such external factors are heterogeneous (Leibowitz and Vitterso 2020 ; Winthorst et al 2020 ).…”
Section: Prior Literaturesupporting
confidence: 84%
“…Harmatz et al ( 2000 ) found depression, hostility, anger and irritability are highest in winter and lowest in summer with females having stronger seasonal variation in wellbeing than males. Some link seasonal variance on wellbeing, to variance in daylight hours and weather conditions, although wellbeing responses to such external factors are heterogeneous (Leibowitz and Vitterso 2020 ; Winthorst et al 2020 ).…”
Section: Prior Literaturesupporting
confidence: 84%
“…The reasons for such unexpectedly low prevalences of SAD in these high latitude populations are uncertain. Some investigators have proposed that some northern populations may have adapted genetically or socially to the conditions (Guðrúnardóttir, 2018; Leibowitz & Vittersø, 2020; Magnusson & Partonen, 2005). Others question whether SAD is sufficiently rigorously defined and/or identified, given various limitations in study designs (e.g., recall bias, self‐selected study samples, comparison of cross‐sectional samples, not accounting for comorbidities and other possible confounders, highly variable between‐ and within‐individual expression and timing of various symptoms; Hansen et al, 2008; Karlsson, 2009; Melrose, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In future research, it may be worth further interrogating this aspect of our findings. For instance, it might be worth examining the moderating role of a positive wintertime mindset on body image outcomes in white natural environments [ 60 ].…”
Section: Discussionmentioning
confidence: 99%